Anti‐Ro52 antibodies in clinical practice: A single‐centre experience. Issue 3 (9th September 2020) - Wu, Si; Tang, Xiaojun; Wu, Liping; Lu, Liangjing; Feng, Xuebing
Abstract: Introductions: To analyse the clinical significance of anti‐Ro52 autoantibodies that target TRIM21 protein and occur in a variety of connective tissue diseases (CTD), 4782 cases with blood tested positive for anti‐Ro52 antibodies between January 2016 and September 2017 in Drum Tower Hospital were enrolled. Methods: Anti‐Ro52 and anti‐Ro60 were measured using the immunoblotting method together with antibodies against other extractable nuclear antigens at the time of the patient's first visit. Results: In this cohort, females accounted for the majority of all subjects (75.9%) and the average age was 47.25 years old. About 97.4% were diagnosed as having various diseases, in which around 2/3 were CTDs. The incidence of CTD in patients with merely anti‐Ro52 was lower than those with both anti‐Ro52 and anti‐Ro60 (54.7% vs 85.5% for all patients and 53.3% vs 87.1% for inpatients, both P  < .0001). Amongst CTDs, the incidence of systemic lupus erythematosus was significantly decreased, while the incidence of inflammatory myositis as well as undifferentiated connective tissue diseases was increased in anti‐Ro52 single‐positive group. For patients with either CTDs or non‐CTDs, respiratory involvement was more common in patients with merely anti‐Ro52 (67.6% vs 34.7%, P  < .0001 and 53.2% vs 36.3%, P  < .01). Sub‐analysis revealed that both interstitial lung disease and pulmonary infection were related to anti‐Ro52 in CTD inpatients ( P  < .0001 and P  < .05). Conclusions: Our study shows that anti‐Ro52 could occur in various clinical conditions. These antibodies may appear in the early stage of CTD with the lung an important target organ, thus their presence warrants long‐term follow‐up.